Analisis Yuridis Pembagian Harta Bersama Setelah Perceraian Ditinjau dari Kompilasi Hukum Islam dan Undang-Undang Perkawinan - Hendarto, Ananda Vania Putri (Universitas Negeri Malang, 2022)
This study aimed to analyze the distribution of joint assets after divorce according to the Compilation of Islamic Law and Marriage Law, as well as judges' considerations regarding the distribution of joint assets in the Bojonegoro Religious Court Decision Number 521/Pdt.G/2018/PA.Bjn. This study used normative juridical research with a statutory approach. The data source was from secondary legal materials—data collection techniques using literature study and analyzed by descriptive techniques. The study results indicated that the Marriage Law did not determine the amount of the distribution of joint property if the husband and wife divorced. According to Article 37 of the Marriage Law, the distribution of joint property after divorce could be based on religious law, customary law, and other laws chosen by each party. According to the Compilation of Islamic Law, the amount of the distribution of joint property after the divorce was one-half of the joint property if there was no marriage agreement. The judge adjudicated the case of the distribution of joint assets in the Bojonegoro Religious Court Decision Number 521/Pdt.G/2018/PA.Bjn gave the defendant and the plaintiff the right under Indonesian laws in a fair way.